Calcinated Ferronickel Slag as Catalyst In Biodiesel Synthesis from Cooking Oil - Sitanggang, Boy Chandra; Aras, Neny Rasnyanti M. (Indonesian Journal of Chemical Research, 2024)
Ferronickel slag is a byproduct of the nickel ore smelter factory that is typically dumped in an open area and is detrimental for the environment. The research objectives are to examine ferronickel slag potential as catalyst in producing biodiesel. Ferronickel slag was prepared by milling followed by sieving 200 meshes and calcinated at 900 ºC. The next step was to evaluate the calcinated slag using XRF, which revealed that the major components were, in order, Si (49.47%), Fe (36.09%), Ca (7.12%), Cr (3.01%), and Mn (2.28%). Slag that has been calcined and utilized in the transesterification of cooking oil as catalyst in three necked flask with oil to methanol ratio is 1:9, reaction times (1, 2, 3 hours) and temperatures (70, 90, 110 oC). Then, the product were tested for water content, density, viscosity, acid number, free fatty acids, total glycerol, percent of methyl esters according to SNI 7182-2015. FTIR showed the presence of peaks at 1743.65 and 1157.29 corresponding to C=O and O-CH3 functional groups.